STATE, TERRITORY AND INDIGENOUS POPULATION - Camacho Monge, Daniel (2019)
In the central topic entitled "State, territory and indigenous population", Carballo and Madrigal conducted a study in the Cabécar-Tayní indigenous population, located in the province of Limón, Costa Rica, to collect and analyze their views of the landscape from their stories of life and the aesthetics of the place, in order to understand the natural, environmental, cultural, ethnic and social spaces in which this population has developed. For its part, Engelman studies from the perspective of public policies, social dynamics of indigenous populations in the municipality of Almirante Brown of the Metropolitan Region of Buenos Aires (RMBA), Argentina, with the objective of documenting the process of visibility and organization local ethnopolitics of these organizations, which has allowed a greater political and ethnic presence, a positive vision of the indigenous and an  empowerment of the population. Barrera-Rojas, Sánchez-Carballo, Ruíz-Sánchez and Ruiz-Guevara, investigate the conditions of poverty faced by indigenous women in the Maya Zone of Quintana Roo, Mexico. For this research, they used three indicators of poverty: Extreme poverty line proposed by the World Bank, Minimum welfare line and Welfare line proposed by the National Council for the Evaluation of Social Development Policy.